Using Schema-Based Diagrams to Represent and Solve Word Problems: Relationship between Elementary Preservice Teachers' Knowledge and Demonstration. (2nd January 2021) - Zhang, Shuang; Wang, Jian; Flores, Raymond
ABSTRACT: The analysis of word problem types and schema-based diagrams are assumed useful for helping students and thus, important for preservice teachers to learn in their preparation programs. Drawing on pre-and post-assessments and videotaped demonstrations, this study analyzed elementary preservice teachers' understanding of addition and subtraction word problem types and how well they could demonstrate their understanding after their exposure in a mathematics methods course. Results suggest that while participants' knowledge of word problem types and their ability to solve word problems were substantially improved, their identification, diagram representations, and solutions for different types of word problems were not substantially developed. Policy and research implications for these findings are then discussed and proposed.